2017
DOI: 10.1007/s10897-017-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Practices of Athletic Trainers and Team Physicians Implementing the 2010 NCAA Sickle Cell Trait Screening Policy

Abstract: Sickle cell trait (SCT) is usually benign. However, there are some conditions that may lead to SCT-related problems and put athletes with the trait at particular risk. In 2010 the National Collegiate Athletic Association (NCAA) issued a policy that required all Division I (DI) student-athletes to confirm their SCT status or sign a liability waiver to opt out of testing. Athletic trainers and team physicians play key roles in the policy implementation and we examined their perceptions and practices. Between Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A number of sports organizations advocate for universal screening prior to participation in high intensity athletics due to rare reported instances of exercise related sudden death 12 . In 2010, the National Collegiate Athletic Association (NCAA) implemented a mandatory opt out sickle trait screening policy prior to athletic participation 13 . However, screening in adults remains controversial due to the potential for loss of employment, insurance, and other forms of discrimination based on sickle trait status.…”
Section: Discussionmentioning
confidence: 99%
“…A number of sports organizations advocate for universal screening prior to participation in high intensity athletics due to rare reported instances of exercise related sudden death 12 . In 2010, the National Collegiate Athletic Association (NCAA) implemented a mandatory opt out sickle trait screening policy prior to athletic participation 13 . However, screening in adults remains controversial due to the potential for loss of employment, insurance, and other forms of discrimination based on sickle trait status.…”
Section: Discussionmentioning
confidence: 99%
“…Sickle cell trait has been associated with rare but severe consequences including rhabdomyolysis and sudden death related to strenuous exercise (9). While the exact pathological cause of SCT leading to death has not been established, it is hypothesized that a combination of high intensity exercise in warm climates, high altitudes, and dehydration may lead to a potentially lifethreatening event (9,50). Complications have been reported in both the military and civilian populations, including college athletes.…”
Section: Sickle Cell Trait Exercise Considerationsmentioning
confidence: 99%
“…In the United States, these conditions are detected during newborn screening, but parents are not typically informed about SCT status unless the information is requested [2]. In general, SCT is more common among people with heritage Sub-Saharan Africa, the Mediterranean region, the Arabian Peninsula, the Caribbean, and South and Central America [3]. In 2015, it was reported that 3 million Americans carry SCT, including 8% of blacks, .5% of Hispanics, and .2% of whites [4].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, National Collegiate Athletic Association (NCAA) introduced a proposal addressing SCT screening [3]. This policy required all NCAA Division I student-athletes beginning their eligibility to provide their institution with accurate information regarding their SCT status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation